Antioxidative and Anti-inflammatory Effect of Gajus (Anacardium Occidentale l.) Leaves Extract on Endothelial Dysfunction in Early Stage of Atherosclerosis - Nik Hasan, Mohd Kamal (2010)
Anacardium occidentale (A. occidentale), also known as Gajus among Malaysian, is a member of the Anacardiaceae plant family which is widespread in Malaysia. In this study, the effects of A. occidentale leaves aqueous extract (AOE) as antioxidative and anti-inflammatory agent on endothelial dysfunction in the early stage of atherogenesis development was investigated using human vein endothelial cells (HUVECs) and isolated human low density lipoprotein particles (LDL) as models. The inhibitory concerntration (IC50) of hydrogen peroxide (H2O2) and effective concerntration (EC50) of AOE in preventing H2O2-induced cell injury were assessed using the MTT assay in order to evaluate cell viability. It was observed that 250 µM of H2O2 reduced cell viability by 50% (IC50). Cytotoxic assessment of AOE was performed by exposing the HUVECs to AOE at concerntration ranging from 50 to 700 µg/mL for 24 hr with complete medium. Anacardium occidentale extract was found to be non-toxic to the cells as no IC50 was obtained. The cells were pretreated with AOE at different concerntrations within the range of 50-700µg/mL for 30 mins followed by 24-hours incubation with H2O2 (250 µM). The EC50 of AOE that protected against H2O2-induced cell injury was found to be 180µg/mL. The antioxidative and anti-inflammatory effects of AOE on H2O2-induced cell injury were further carried out by seeding HUVECs in 6-well plates and divided them into three groups; positive control, negative control, and treated groups. In the positive control (PC) group, HUVECs were exposed to either 250 µM H2O2 or 10ng/mL TNF-α alone, whereas in the treated groups HUVECs were treated with various concentrations of AOE (100, 180, 250 and 300 µg/mL) for 30 minutes prior to expose to H2O2 (250 µM) or TNF-α (10ng/mL). In the negative control (NC) groups, HUVECs were incubated with culture medium only. The cells were incubated for 24 hours at 37° C with 5% CO2 supply for analysis of NO, NF-кB, VCAM-1, MMP-9, MCP-1 and M-CSF. The AOE doses within the concerntration range 100-300µg/mL protected against cellular damage and prevented microsomal lipid peroxidation in H2O2- induced HUVECs as indicated by low MDA levels. The treatment with AOE at concentrations ranging from 250 and 300 µg/mL caused significant reduction in the anti-oxidative enzyme (SOD, GPx and Catalase) activities (p<0.05/p<0.01) with concomitant reduction of NO production in comparison with the PC. Besides that, the expressions of VCAM-1, ICAM-1, MMP-1, MCP-1 and M-CSF in the AOE-treated groups were lowered (p<0.05/p<0.01) whereas NF-кB was inactivated in comparison with the respective expressions in the non-treated counterparts. Furthermore, application of AOE at concentration within the range of 250 and 300 µg/mL to be isolated LDL particles prevented the lipid peroxidation processes and protected against LDL oxidation as was as indicated by low MDA formation. These findings suggest that AOE possesses antioxidative and anti-inflammatory properties and that it attenuate the initial stage of atherogenesis in vitro. Inhibition of NF- кB activation could be the possible underlying mechanism in modulating early events of atherogenesis.